2022
DOI: 10.1155/2022/6357421
|View full text |Cite
|
Sign up to set email alerts
|

Partial Differential Equation-Assisted Accounting Professional Education and Training Artificial Intelligence Collaborative Course System Construction

Abstract: In this paper, we use partial differential equations combined with artificial intelligence methods to conduct an in-depth study and analysis of the curriculum system of accounting and finance professional education and training. Under the condition of high-performance advanced computers, neural network technology has been developed rapidly and started to adapt to the requirements of computational accuracy and speed in the field of PDEs. Neural networks have good self-learning as well as self-adaptive capabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…States are facing the reality that several campuses may not be viable in their current form for much longer. Hu (2022) suggests artificial intelligence needs to become an increased portion of accounting education. Artificial intelligence and accounting education was also studied by Dangi and Saat (2021; and they found that it is unlikely for educational technology experience to impact accounting educators' adoption of technology.…”
Section: Regional Public Universitiesmentioning
confidence: 99%
“…States are facing the reality that several campuses may not be viable in their current form for much longer. Hu (2022) suggests artificial intelligence needs to become an increased portion of accounting education. Artificial intelligence and accounting education was also studied by Dangi and Saat (2021; and they found that it is unlikely for educational technology experience to impact accounting educators' adoption of technology.…”
Section: Regional Public Universitiesmentioning
confidence: 99%